Design and Implementation of a Web-Based Currency Converter System Using an Application Programming Interface - Purwadi; Augst Nurandini; Gusnaeni Indah Pratiwi (Yayasan Kita Menulis, 2026)
This study aims to design and implement a web-based currency converter application that utilizes an Application Programming Interface (API) to provide real-time and accurate exchange rate data. The increasing intensity of global economic activities has created a growing need for fast and reliable currency conversion, while manual conversion methods are prone to errors and data inconsistencies. This research employs the Research and Development (R&D) approach using the waterfall development model, which includes requirement analysis, system design, implementation, testing, and maintenance. The developed application provides two main features: an exchange rate calculator that performs automatic currency conversion based on real-time data, and a currency exchange history feature that presents exchange rate trends in graphical form within a selected period. Testing results indicate that the application runs reliably, delivers fast responses, and consistently displays up-to-date exchange rate information. In conclusion, the proposed application serves as an effective web-based solution for accessing accurate currency exchange information to support international financial activities.